IMPROVEMENT OF GEOTECHNICAL PROPERTIES OF COHESIVE SOIL USING CRUSHED CONCRETE - Karkush, Mahdi O.; Yassin, Sarah (Civil Engineering Journal, 2019)
Some natural resources such as gravel are not renewable, therefore, it is necessary to reduce the use of such resources and replace them with other recycled, economic, and environmentally friendly materials. Recycled crushed concrete aggregates demolished from old buildings and blocks of waste concrete can be used to replace the natural aggregates. The present study focused on using recycled crushed concrete in improvement the chemical and geotechnical properties of soft soil having undrained shear strength of 6.78 kPa. The soft soil samples were mixed with 5, 10, and 15% of crushed concrete. The blocks of waste concrete are grinded by mills to get crushed concrete which passing sieve no. 4. Such aggregates are lighter than natural aggregates and provide a good deformation modulus when mixed with soil. In Iraq, there are hundred thousand tons of concrete blocks used as fences and now considered wastes after removing these security fences, so it?s important to interest from recycling of such materials to be used in the improvement wide region of soft soils in Iraq. The results of tests showed increasing the undrained shear strength of soft soil by 175-193.5% and reduced the compressibility of soft by 25-31% measured in terms of compression index.